Decision Support System for WP and MOORA Methods in Determining Performance Assessment of Outstanding Education Personnel - Mesran, Mesran; Jaafar, Mime Azrina; Rosnizam, Rosnizam (Forum Kerjasama Pendidikan Tinggi, 2026)
Employee work performance on this date the education staff (Tendik) as a determinant of the success of the performance of the Public Service Agency (BLU). Students who have a good leadership spirit, which are listed as outstanding and superior tendik competencies, are expected to be able to spur other students to achieve as well. The assessment of the achievers is based on the provisions of Permendikbud No. 30 of 2018. Form F5 in the attachment of the Minister of Education and Culture Number. 30 of 2018 becomes an assessment variable in the educational activity support system. Work Achievement of Education Personnel is a major factor in the success of higher education performance. Good work results will have a good impact on universities. Educational staff who excel are also competent in higher education also support both the education staff and universities. Rewards or awards given to Education Personnel can be done by assessing the performance results of each Education Personnel. Rewards are given to Education Personnel as a form of appreciation for the performance carried out at universities. rewards to Education Personnel must be based on appropriate and accurate assessments. The problems found do not have to be used to evaluate the Education Personnel in presenting prizes. The performance assessment carried out must be objective, of course, with an objective assessment the results obtained on the educational performance assessment are not a problem for the education staff. Decision Support System is a computer-based information system that is used to assist in decision making by utilizing certain data and models to support a solution in solving a semi-structured and non-structured problem. The MOORA (Multi Objective Optimization On The Basis Of Ratio Analysis) and WP (Weighted Product) methods are methods in the Decision Support System that provide relatively precise results to the determined assessment. Research with the MOORA and WP procedures used produces and provides an assessment so that it can provide decision support to award outstanding Education Personnel